Aviation‐based teamwork skills work for surgeons: time for an 'aviation bundle'?. Issue 12 (10th October 2018) - Pal, Atanu; Lal, Roshan; Frizelle, Frank
Abstract : Background: Aviation systems were developed to improve safety and have achieved remarkable results. Medicine has looked to replicate these systems; however, the gap in outcomes between the two industries remains vast. Bridging this chasm requires an in‐depth analysis of the applicability of the aviation safety model in surgery. This study uses qualitative methods to explore how aviation‐based practices may be adapted and applied more effectively in theatre. Methods: Data were collected using multiprofessional focus groups in a single centre. The focus groups involved discussion around teamwork and aviation‐based non‐technical skills. With consent, audio recordings were anonymized and transcribed. Qualitative (thematic) analysis was used to identify themes. Results: Five focus groups were conducted. Eight themes emerged, with a total of 18 sub‐themes. Themes were: current practice, customization, applicability, team performance, human factors, analogy, incidents and integration of skills. Extent and limitations of the aviation surgery analogy also emerged. Conclusions: The new insights gained through this qualitative analysis highlight the need to tailor aviation‐based practices to the operating theatre. To achieve this, we propose the 'aviation bundle' of non‐technical skills. This blueprint aims to promote a culture of safety and efficiency in surgical practice and could be developed into a training programme for theatre staff.